Synopsis of Nothybidae (Diptera: Brachycera) from China, with redescription of Nothybus absens Lonsdale & Marshall - Zhou, Jiale; Marshall, Stephen A.; Yang, Ding (Zootaxa, 2021)
The Nothybidae of China are reviewed, including Nothybus absens Lonsdale & Marshall, 2016 which was previously known only from photographs, is here redescribed on the basis of male and female specimens. A key to Chinese species of Nothybidae is provided.